Talking to the senses: modulation of tactile extinction through hypnotic suggestion - Maravita, Angelo; Cigada, Mario; Posteraro, Lucio (Frontiers in Human Neuroscience, 2012)
Brain damage can significantly impair the processing of sensory events. In particular, patients affected by extinction to double bilateral stimulations, show reduced awareness of stimuli delivered in the space contralateral to the brain lesion, when these are presented in competition with ipsilesional ones. The present work shows that hypnotic suggestion can temporarily improve tactile extinction. Patient EB showed an improved detection of contralesional targets after a single 20-minute hypnosis session, during which specific suggestions were delivered with the aim of increasing her insight into somatosensory perception on both sides of the body. Simple overt attention orienting towards the contralesional side, or a hypnotic induction procedure not accompanied by specifically aimed suggestions, were not effective in modulating extinction. The present result is the first systematic evidence that hypnosis can temporarily improve a neuropsychological condition, namely extinction, and may open the way for the use of this technique as a fruitful rehabilitative tool for brain-damaged patients affected by neuropsychological deficits.